The combined use of Raman and micro-X-ray diffraction analysis in the study of archaeological glass beads - Costa, Mafalda (2019)
This study proposes a new nondestructive methodology that combines micro‐Raman spectroscopy and micro‐X‐ray diffraction (μ‐XRD), complemented by variable pressure scanning electron microscopy coupled with energy dispersive X‐ray spectrometry, to determine the composition of glass artifacts and the manufacturing techniques employed in their production. The use of micro‐Raman spectroscopy revealed that most samples belong to the alkaline glass family. Chemical analysis also allowed the identification of the main colorants used in the manufacture of the glass beads in this study. Dark blue and turquoise glass were colored using cobalt ions and copper ions, respectively. Amber or light brown hues were produced using the iron–sulfur amber chromophore. Iron ions were also used to produce green, yellow, cream‐colored gray, and black hues. White glass was produced using calcium antimonate phases. These compounds, identified by micro‐Raman spectroscopy and μ‐XRD, were also used as opacifying agents. This study highlights the importance of using micro‐Raman spectroscopy in the study of ancient glass artifacts. In fact, micro‐Raman spectroscopy not only allows the determination of the glass family of heavily degraded samples but was also found to be the only technique capable of identifying evidences of the rearrangement of the silicate network following selective leaching. The combined use of micro‐Raman spectroscopy and μ‐XRD permitted the identification of the opacifying agents and heat treatment used in the manufacture of the opaque glass beads in this study.